(untitled) (Discourse of Law and Administration, 2022)
The article deals with the problem of the functioning of the highest representative assemblies in the period of the 16th-18th centuries in the territory of the Holy Roman Empire of the German Nation. Particular attention was paid to the form, structure and functioning of the highest of them. It is about the Parliament of the Reich and Parliaments of the Reich Circles. In this aspect, attempts were made to show the role and importance of the broad and multi-level social group of the counts. The assemblies, on the other hand, were selected from the broad parliamentary system of the Habsburg state, because of their ultimate decision-making and close connection, their natural importance or the existence in their structure separate from other aristocratic groups, clergy and city benches. As a result, their voice did not drown in the general decisions of the nobility as a whole.